The effect of recreational physical activity on some of the emotional characteristics of middle school students (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare a recreational physical program that is compatible with the research sample. And to identify some of the emotional features (depression, nervousness, susceptibility to excitability), and to identify the effect of the recreational physical program on the emotional features under study. The researcher used the experimental method with two equal groups (the control and the experimental group), and it was applied to 60 female students from (Al-Izdihar Secondary School for Girls), the second intermediate grade. The researcher used the Freiburg Personality Scale in its three dimensions (depression, nervousness, excitability) as well as preparing a recreational physical program. The recreational physical activity program took 8 weeks, with two units per week for 45 days.